BAURAN PEMASARAN BUAH DURIAN DI KAWASAN BOULEVARD MALL, KOTA MANADO - Revo Yefta Sumampow; Caroline B. D. Pakasi; Lyndon ., Pangemanan (Sam Ratulangi University, 2016)
The purpose of this study was to identify elements in